Meningkatkan Kepercayaan Diri Siswa dengan Menggunakan Model Pembelajaran Langsung di Sekolah Dasar - Farhatunnisa Farhatunnisa; Ramdhan Witarsa; M. S yahrul Rizal (Universitas Negeri Makassar, 2022)
Abstrak. This study aims to increase students' self-confidence by using the direct learning model in elementary schools. The research method used is the classroom action research method, with the steps of planning, implementing, observing, and reflecting. The research subjects were 22 students, consisting of 10 male students and 12 female students. Data collection techniques used are observation and documentation. The research instrument used was the teacher activity observation sheet and the student activity observation sheet. The data analysis technique was carried out using quantitative and qualitative data analysis techniques. The results showed that there was an increase in students' self-confidence from pre-action to cycle 1 by 30%. The increase in students' self-confidence also occurred in cycle 1 to cycle 2 by 10%. The conclusion of this study is that the application of the direct learning model can increase the overall self-confidence of students by 40%. The direct learning model with video media needs to be continued by the teacher because with the direct learning model with video media students become more confident in participating in learning. The use of video media can facilitate the needs of elementary school students who are still thinking at a concrete operational level.